Analysis of the Relationship Between Learning Motivation and English Learning Achievement - Annisa Rahmadira; Wilda Hanifah Fitri; Salsabila Khairani; Zazqia Desmitha; Larissa Yukika Yulanda Putri; Mainar Fitri (Jurnal Ilmiah Profesi Pendidikan, 2026)
Learning motivation is one of the factors that influence students' success in achieving academic achievement, especially in English. Low learning motivation can cause students to be less active, less diligent, and less enthusiastic in participating in the learning process, resulting in low learning achievement. This study aims to analyze the relationship between learning motivation and English learning achievement based on various theories and previous research results. The study uses a qualitative approach with a library research type. Data were collected through documentation studies by reviewing books, journal articles, theses, and other relevant scientific sources. Data analysis was carried out using descriptive-analytical techniques through the stages of data collection, filtering, grouping, analysis, and interpretation. The results of the study indicate that learning motivation has a positive relationship with English learning achievement. Students who have high intrinsic and extrinsic motivation tend to be more active in learning, more disciplined in learning, and more consistent in developing English language skills, thus achieving better learning achievement. In addition to motivation, learning achievement is also influenced by initial abilities, learning strategies, the learning environment, and family support. This study shows that increasing learning motivation is one of the efforts that can support improving students' English learning achievement.